Interaction of vectors and parental viruses with the host genome - Gil-Fariña, Irene; Schmidt, Manfred (Current opinion in virology, 2016)
Viral replication by acquisition of the host cell biology represents a central part of a virus life cycle. Thereby, integration into the host genome constitutes a successful strategy to ensure viral persistence and viruses have developed different mechanisms to integrate and benefit from cell's transcriptional and translational machinery. While lentiviral (e.g. HIV) integration is influenced by the chromatin landscape encountered upon nuclear entry, certain parvoviruses (e.g. AAV) integrate specifically within genomic regions bearing increasingly known sequence motifs. Gene therapy exploits these viral persistence strategies to achieve efficient and safe long-term transgene expression. Here we focus on two widely used vectors and their parental viruses, HIV and AAV, to discuss recent insights into lentiviral vector oncogenicity by alteration of endogenous transcripts as well as the unresolved AAV vectors genotoxic potential.